Implementation Of Public Information Disclosure Policy (Kip) Through The Village Information System (Sid) In Bandung District (Case Study In Kutawaringin District) - Raya Mustiraya; Ine Agustine; Lita Amelia Djuwita (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The research conducted by the researcher is located in Kutawaringin District, Bandung Regency. The background of this research is to determine the extent to which the implementation of public information disclosure policies have been implemented in village public bodies, to see whether the Public Information Policy has been implemented through the Village Information System. The research method used by the researcher is a qualitative method with case studies, with data collection techniques carried out by researchers, namely by means of observation, interviews, and document studies. The theory that will be used as a guide in this research is the theory of policy implementation from George C. Edward III and public information that must be published according to Law No. 14 of 2008 concerning Openness of Public Information. The results of the study indicate that the policy of public information disclosure through the village information system in the villages of the Kutawaringin sub-district has not been implemented properly, this is due to disturbances in transmission in communicating the substance of the policy, the capacity of human resources in the village is not yet ready to implement the policy, the village head does not understand the importance of implementing the policy so that the delegation of orders is not binding and there is no effort to make it happen, either the formation of regulations, team formation, funding, or consistency in its implementation.